The aesthetics of the mask in the collection of Alienation by Jaafar al- Tayyar by the poet Youssef oueghlissi - hadibi, abire; djaghdi, Abd elSalam (El Omda in Linguistics and Discourse Analysis, 2022)
Abstract : This study seeks to reveal the manifestations of the aesthetics of the mask in the arabic poem, and whoever contemplates this creative achievement finds that the language of the poem has shifted from direct rhetorical language, and the mask technique has taken a wide space in the poetry of modernists in order to break out of the circle of familiar. and return to Diwan The Alienation Of Jaafar al- Tayyar by the Poet Yousef Oueghlissi, we find that suggestive energy that the poems possess.